Dune [compact disc, unabridged] - Herbert, Frank (Herbert, Frank. Dune chronicles, 2007)
The first book of the Dune chronicles is set on the desert planet Arrakis and begins with the story of Maud'dib, a hero who will guide his great family in establishing the perfect society.